Stand-off Detection of Suicide Bombers and Mobile Subjects - Schubert, Hiltmar; Rimski-Korsakov, A. (Nato Security through Science Series B, Physics and Biophysics, 2006)
These proceedings contain the presentations of a NATO-Russian - vanced Research Workshop (ARW) held at the Fraunhofer Institute for Chemical Technology (ICT) near Karlsruhe, Germany, attended also by most of the members of the "Explosive Detection Working Group" (EDWG) of the "Advisory Panel on Security-Related Civil Science and Technology". The ARW, approved by the NATO Science Committee, is the ?fth NATO- Workshop during the last 3 years dealing with the detection of explosives in connection with counter-terrorism. The special goal of this workshop was the exchange of knowledge and experiences in the special ?eld of "Stand-Off Detection" and to ?x the "State of the Art" in this ?eld of research. At the end of the workshop proposals of Research & Development were presented (but not included in the proceedings), which were eva- ated by the present members of the EDWG during the following day of the workshop. One of the ?rst measures to counter the threat will be to stop the transport of illicit materials, that means in our case to detect explosive charges before they are initiated by terrorists.